Somatomedin in growth disorders and chronic renal insufficiency in children. - Schwalbe, S L (1977)
Somatomedin activity was measured using an embryonic chick cartilage assay in 33 normal and short normal children, 23 children with pituitary growth hormone (GH) deficiency, 14 children with sexual precocity, and 13 children with chronic renal insufficiency. In normal children somatomedin activity correlated well with chronological age: low valles in early childhood rose to higher than adult levels at puberty. Children with GH deficiency had significantly lower activities and those with sexual precocity significantly higher activities than normal children. In all three groups somatomedin activity correlated well with bone age. In children with chornic renal insufficiency there was a significant correlation between decreasing somatomedin activity and both a reduced growth velocity and a falling glomerular filtration rate. Somatomedin activity and growth velocity were within normal limits in children with glomerular filtration rates above 30 ml/min/1-73 m2.